The Survival of Mandailing Angkola Language Ecolexicon in Kuling-Kuling Anca Song Lyrics - Azhary Tambusai; Khairina Nasution (PT Inovasi Pratama Internasional, 2024)
This research is a qualitative research that discusses the survival of the Angkola Mandailing language ecolexicon. This research uses the study of ecolinguistics and lexical semantics. This research data is in the form of Kuling-kuling Anca song lyrics. The data were analyzed using the distributional method. The results of this study indicate that the ecolexicon in Kuling-Kuling Anca song lyrics are parahu 'boat', kukang 'loris', pahu 'fern plant', bulu 'bamboo tree', and rambutan 'rambutan fruit'. These five lexicons still survive in Angkola Mandailing because the song Kuling-Kuling Anca is often played in the Angkola Mandailing area and these lexicons are also still found in the area. From the results of this study, it is known that the introduction of regional lexicons through a song is very effective to preserve the shifting or extinct language lexicon.